Diaphragm for secondary battery and preparation method thereof
By modifying the PDA on the surface of MOFs nanoparticles and using a carboxyl-based binder cross-linking reaction, the problem of difficult to reduce the amount of binder in the prior art is solved, and a separator with high peel strength and low internal resistance is achieved, and the electrochemical performance of the battery is improved.
Patent Information
- Application Number
- CN202510309685.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively reduce the amount of adhesive while ensuring the peel strength of the separator, resulting in a large internal resistance of the battery and affecting lithium ion migration.
By modifying the PDA on the surface of MOFs nanoparticles and selecting carboxy-based binders, vacuum drying conditions are controlled to promote the cross-linking reaction between PDA and carboxy-based binders, and the compatibility between MOFs nanoparticles and polymer film is improved, thereby reducing the amount of binder.
It realizes the reduction of the amount of adhesive while ensuring peeling strength, reduces the internal resistance of the battery, improves the ionic conductivity, and enhances the wetting and thermal stability of the diaphragm.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a diaphragm for a secondary battery and a preparation method thereof. Background Art
[0002] With the vigorous development of the new energy industry, the importance of the separator as an indispensable component of the internal structure of the battery is becoming increasingly prominent. At present, polyolefin separators have been widely used in commercial lithium batteries due to their excellent mechanical properties, outstanding electrochemical stability and good processing performance. Since polyolefin materials themselves have limitations in thermal stability and electrolyte wettability, in order to overcome these limitations, the existing technology widely uses inorganic ceramic particles (such as alumina, boehmite, titanium dioxide, magnesium hydroxide, etc.) to modify the surface of polyolefin separators by coating. This is an effective and commonly used method that can promote the migration of lithium ions to a certain extent, but it has not completely solved the problems of thermal stability and electrolyte wettability of polyolefin materials. In addition, these inorganic particles have a high density, and when they are used for coating modification, they will also reduce the energy density of the battery.
[0003] In this context, metal organic framework materials (MOFs), as a new type of porous material, are widely used in various fields due to their high porosity, high specific surface area and excellent thermal stability. Applying MOFs to the membrane coating can not only achieve a smaller surface density at the same thickness, thereby improving the battery energy density, but also significantly improve the wettability of the membrane and reduce the internal resistance of the battery.
[0004] Compared with traditional ceramic materials, MOFs have significant advantages as coating materials. Its high porosity and specific surface area greatly improve the absorption and retention rate of the electrolyte, greatly reducing the transmission resistance of ions inside the material, thus performing excellently in optimizing ion conductivity. At the same time, MOFs have extremely excellent thermal stability, and the decomposition temperature is usually above 400°C. It can maintain structural integrity at high temperatures, significantly improving the safety and service life of the battery. In addition, on the basis of ensuring heat resistance, the low density characteristics of MOFs make the prepared heat-resistant layer smaller and thinner, which is further conducive to the improvement of battery energy density.
[0005] Patent CN118659091A discloses a method for preparing a MOFs-based coating film, specifically a slurry preparation including Cd-MOF, dispersant, binder, thickener, and wetting agent, and then the slurry is coated on the surface of a PE-based film to prepare a diaphragm with high liquid absorption and liquid retention and flame retardant properties. The results show that the ionic conductivity of the diaphragm is below 0.9mS / cm, that is, the internal resistance of the diaphragm is large, which is not conducive to lithium ion migration. The possible reason is that too much binder (8.8-11wt%) is added when preparing the slurry, which will block the channels between the particles. In order to improve the electrochemical performance, it is necessary to reduce the amount of binder, but directly reducing the amount of binder will be accompanied by a decrease in peel strength. How to use less binder while ensuring peel strength is a difficulty in the industry.
[0006] Therefore, a secondary battery separator and a preparation method thereof are needed to solve the above problems, which is of great significance. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the prior art and to provide a secondary battery separator and a preparation method thereof.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a secondary battery separator, comprising coating a slurry on the surface of a polymer film, and vacuum drying the slurry to prepare the secondary battery separator, wherein the slurry contains 15-40 wt% of PDA@MOFs, 1-6 wt% of a binder and water;
[0010] PDA@MOFs are PDA (polydopamine)-coated MOFs nanoparticles;
[0011] The binder is a carboxyl binder;
[0012] The vacuum drying temperature is 20-150°C and the time is 8-24h.
[0013] In view of the problem that the prior art cannot use less adhesive while ensuring peel strength, the present invention solves the problem by modifying PDA on the surface of MOFs nanoparticles and selecting a carboxyl adhesive as a binder. PDA has negatively charged oxygen-containing functional groups and can have a strong electrostatic force with the metal ions in the MOFs nanoparticles. At the same time, controlling the temperature and time of vacuum drying can cause a cross-linking reaction between PDA and the carboxyl adhesive, thereby increasing the compatibility of the MOFs nanoparticles and the polymer film. Even if the amount of adhesive is reduced, the MOFs nanoparticles can still adhere to the polymer film well, so that the peel strength between the MOFs nanoparticles and the polymer film is higher.
[0014] As the preferred technical solution:
[0015] In the method for preparing a secondary battery separator as described above, the thickness of the PDA coating layer in PDA@MOFs is 1-30 nm; the preparation steps of PDA@MOFs are as follows:
[0016] (a) dissolving a metal salt and an organic ligand in a solvent to obtain a solution A and a solution B respectively, mixing the solution A and the solution B and reacting them at a certain temperature and pressure, and obtaining MOFs nanoparticles through post-treatment (centrifugation, washing, drying, drying temperature of 20-80°C, drying time of 6-24h);
[0017] (b) Dopamine, water and buffer solution are mixed to prepare a precursor solution, into which MOFs nanoparticles are added for self-polymerization to obtain PDA@MOFs.
[0018] MOFs nanoparticles are easy to self-agglomerate due to their small particle size and large specific surface area, and are difficult to disperse evenly during slurry preparation. The present invention introduces PDA on the surface of MOFs nanoparticles by solution polymerization, so that the MOFs nanoparticles can be more evenly dispersed in the slurry.
[0019] In the method for preparing a secondary battery separator as described above, in step (a), the metal salt is a Co salt or a Zn salt;
[0020] The organic ligand is a nitrogen-containing heterocyclic ligand (2-methylimidazole, 4,4'-bipyridine, etc.) or a carboxylic acid ligand (terephthalic acid, trimesic acid, etc.);
[0021] The molar ratio of the metal salt to the organic ligand is 1:1-10;
[0022] The reaction temperature is 20-150°C and the reaction time is 8-24h;
[0023] The porosity of MOFs nanoparticles is 58-81% and the specific surface area is 471-1123m 2 / g, pore size is 4-18nm;
[0024] In step (b), the buffer is tris hydrochloride buffer, phosphate buffer or bicarbonate buffer;
[0025] The concentration of dopamine in the precursor solution is 1-3 mg / mL;
[0026] The pH value of the precursor solution is 8-9.5;
[0027] The self-polymerization reaction temperature is 20-40°C, and the self-polymerization reaction time is 1-24h.
[0028] In the method for preparing a secondary battery separator as described above, the carboxyl binder is one or more of PAA (polyacrylic acid), carboxymethyl cellulose, and alginate.
[0029] In the method for preparing a secondary battery separator as described above, the slurry further contains 0.1-0.5wt% of a surfactant, and the surfactant is a sulfate ester salt or a sulfosuccinate salt.
[0030] In the method for preparing a separator for a secondary battery as described above, the polymer film is a polyolefin (polypropylene, polyethylene) separator, a cellulose film, a polyimide film or a polyacrylonitrile film, and has a thickness of 7-16 μm.
[0031] In the method for preparing a secondary battery separator as described above, the slurry is coated on one side or both sides of the polymer film, and the thickness of the coating on one side is 2-4 μm.
[0032] In the method for preparing a secondary battery separator as described above, coating is performed by micro-gravure coating or wire rod coating.
[0033] The present invention also provides a secondary battery separator, which is prepared by the method for preparing a secondary battery separator as described in any one of the above items.
[0034] As the preferred technical solution:
[0035] A secondary battery separator as described above, wherein the surface density of the secondary battery separator is 6-10 g / m 2 The electrolyte absorption rate is 578-653%. Due to the high porosity of MOFs nanoparticles and the small amount of binder used, the ionic conductivity of the membrane is relatively high, with an ionic conductivity of 1.29-1.52mS / cm and a peel strength of 100-120N / m. After being placed at 150°C for 1h, the longitudinal thermal shrinkage rate is <2%, and after being placed at 150°C for 1h, the transverse thermal shrinkage rate is <2%.
[0036] Beneficial effects:
[0037] The present invention modifies MOFs and utilizes the cross-linking of the coating material and the adhesive to ensure the peel strength while using less adhesive, thereby reducing the internal resistance of the battery, improving the ion conductivity, and better exerting the characteristics of the functional material MOFs itself. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0039] In order to ensure that the properties of the materials used in each embodiment and comparative example are fully disclosed, the manufacturers and brands of the materials are indicated, and products of other manufacturers and brands that meet the requirements of the present invention are also feasible.
[0040] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:
[0041] Electrolyte absorption rate: The secondary battery separators prepared in each embodiment and each comparative example were cut into an area of 50 mm×50 mm as samples, and then the mass of the samples was weighed and recorded as m0 (in g). Then, the samples were immersed in a beaker filled with an electrolyte (1M LiPF6, EC:DMC:EMC=1:1:1, Vol%), and the mass after immersion was weighed and recorded as m (in g) after standing for 1 hour. Finally, the liquid absorption rate w (in mass percentage (%)) was obtained by calculation. According to the above steps, three samples with the same performance were tested and their average value was calculated; wherein, the calculation formula for the liquid absorption rate is: w=[(m-m0) / m0]×100%.
[0042] Ionic conductivity: The secondary battery separators prepared in each embodiment and each comparative example were used as samples, and then the samples were cut into discs with a diameter of 19 mm using a slicer. The discs were assembled into button batteries using a CR2032 battery shell in a glove box filled with argon gas, and finally tested using an electrochemical workstation (AUTOLAB, Switzerland) (test conditions: frequency range 1 Hz~1 MHz, amplitude 5 mV). Finally, the ionic conductivity σ (in Siemens per centimeter (S / cm)) was calculated based on the measured data. The calculation formula is: σ=d / (R×S), where d is the thickness of the disc (in cm), R is the resistance of the disc (in Ω), and S is the effective contact area of the disc (i.e., 1.96 cm 2 ).
[0043] Peel strength: The secondary battery separators prepared in each embodiment and each comparative example were cut into an area of 2 cm×30 cm as samples, and then 3M tape was affixed to the coated surface, and the other side was adhered to a steel plate with double-sided tape. The samples were then tested using an electronic universal testing machine (CMT-6104), and the test results were read on the instrument. Three samples with the same performance were tested according to the aforementioned steps and their average values were calculated; wherein the test speed was 300 mm / min and the stroke was 220 mm.
[0044] Thermal shrinkage: The secondary battery separators prepared in each embodiment and each comparative example were cut into 15 cm × 15 cm squares as samples, and then the longitudinal and transverse directions (MD direction and TD direction) were marked. A 100 mm measuring line was drawn in the center of the sample, and the lengths of MD and TD were measured, recorded as d1 and d2, and then the sample was clamped by 5 A4 papers on the top and bottom, and placed in a 150°C blast drying oven for 1 hour. After cooling to room temperature, the lengths of MD and TD were measured, recorded as dMD and dTD. Finally, the transverse thermal shrinkage and longitudinal thermal shrinkage were calculated by the calculation formula. According to the above steps, three samples with the same performance were tested and their average values were calculated; wherein, the calculation formula of the longitudinal thermal shrinkage is: longitudinal thermal shrinkage = [(d1-dMD) / d1] × 100%, and the calculation formula of the transverse thermal shrinkage is: transverse thermal shrinkage = [(d2-dTD) / d2] × 100%.
[0045] Example 1
[0046] A method for preparing a secondary battery separator, comprising the following steps:
[0047] (1) Preparation of PDA@ZIF-67;
[0048] (1.1) Dissolving cobalt nitrate hexahydrate and 2-methylimidazole in anhydrous methanol to obtain solution A and solution B, respectively. Mixing solution A and solution B, reacting at 25°C and normal pressure (i.e., 0.1 MPa) for 12 h, and post-treating (centrifugation, washing, and drying) to obtain MOFs nanoparticles; wherein the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:8, the drying temperature is 60°C, and the drying time is 8 h;
[0049] The porosity of the obtained MOFs nanoparticles is 73% and the specific surface area is 956m 2 / g, average pore size is 6nm;
[0050] (1.2) dopamine, water, and tris(hydroxymethyl)aminomethane hydrochloride) buffer were mixed to prepare a precursor solution with a pH value of 8.5, and the MOFs nanoparticles prepared in step (1.1) were added thereto and subjected to self-polymerization reaction at 25°C for 2 hours to obtain PDA@ZIF-67; wherein the concentration of dopamine in the precursor solution was 2 mg / mL, and the concentration of the buffer solution in the precursor solution was 0.1 mol / L;
[0051] The thickness of the PDA coating layer in the obtained PDA@ZIF-67 was 3 nm;
[0052] (2) First, 35 wt% of PDA@ZIF-67 prepared in step (1), 2.2 wt% of PAA (manufacturer: Fujian Blue Ocean Black Stone New Material Technology Co., Ltd., brand: BOBSive 288C), 0.2 wt% of sodium dodecyl sulfate and the remainder of water were mixed evenly to obtain a slurry, and then the slurry was coated on one side of a polyethylene separator (porosity: 40%, thickness: 9 μm) by micro-gravure coating, and then vacuum dried at 60° C. for 12 h to prepare a separator for a secondary battery; wherein the thickness of the coating on one side was 3 μm.
[0053] The surface density of the secondary battery separator finally obtained is 7.13 g / m 2 The electrolyte absorption rate is 653%, the ion conductivity is 1.52mS / cm, the peel strength is 120N / m, the longitudinal heat shrinkage rate is 1.5% after being placed at 150℃ for 1h, and the transverse heat shrinkage rate is 1.3% after being placed at 150℃ for 1h.
[0054] Comparative Example 1
[0055] A method for preparing a secondary battery separator is basically the same as Example 1, except that step (1) is not performed and the PDA@ZIF-67 in step (2) is replaced by an equal mass of aluminum oxide.
[0056] The surface density of the secondary battery separator finally obtained is 9.54 g / m 2 The electrolyte absorption rate is 256%, the ion conductivity is 0.86mS / cm, the peel strength is 43N / m, the longitudinal heat shrinkage rate is 9.6% after being placed at 150℃ for 1h, and the transverse heat shrinkage rate is 8.8% after being placed at 150℃ for 1h.
[0057] By comparing Comparative Example 1 with Example 1, it can be seen that the surface density of the secondary battery diaphragm prepared in this comparative example increases, the electrolyte absorption rate, ion conductivity and peel strength decrease, and the longitudinal and transverse thermal shrinkage rates increase. This is because, compared with aluminum oxide, MOFs material is a porous structure with a larger porosity and specific surface area, which improves the electrolyte absorption rate, greatly reduces the ion transmission resistance inside the material, and has a higher ion conductivity. In Comparative Example 1, at a low binder content, the compatibility of aluminum oxide with the base film is poor, resulting in a decrease in peel strength and easy problem of coating shedding, which in turn leads to an increase in thermal shrinkage and a decrease in thermal stability. In addition, due to the lower specific gravity of MOF, the surface density of the prepared secondary battery diaphragm will be smaller and thinner than that of aluminum oxide.
[0058] Comparative Example 2
[0059] A method for preparing a secondary battery separator is basically the same as Example 1, except that: step (1.1) is not performed, the MOFs nanoparticles in step (1.2) are replaced by an equal mass of aluminum oxide; the PDA@ZIF-67 in step (2) is replaced by an equal mass of PDA@Al prepared in this comparative example 2 O 3 .
[0060] The surface density of the secondary battery separator finally obtained is 9.67 g / m 2 The electrolyte absorption rate is 268%, the ion conductivity is 0.83mS / cm, the peel strength is 87N / m, the longitudinal heat shrinkage rate is 2.8% after being placed at 150℃ for 1h, and the transverse heat shrinkage rate is 2.6% after being placed at 150℃ for 1h.
[0061] Comparing Comparative Example 2 with Example 1, it can be seen that the surface density of the secondary battery separator prepared in this comparative example increases, the electrolyte absorption rate, ion conductivity and peel strength decrease, and the longitudinal and transverse thermal shrinkage rates increase. Comparative Example 2 has better peel strength and thermal shrinkage than Comparative Example 1 because the aluminum oxide is coated with PDA.
[0062] Comparative Example 3
[0063] A method for preparing a secondary battery separator is basically the same as that in Example 1, except that the vacuum drying condition in step (2) is: vacuum drying at 25° C. for 1 h.
[0064] The peel strength of the secondary battery separator finally obtained was 54 N / m, the longitudinal heat shrinkage rate was 6.9% after being placed at 150° C. for 1 hour, and the transverse heat shrinkage rate was 6.0% after being placed at 150° C. for 1 hour.
[0065] By comparing Comparative Example 3 with Example 1, it can be seen that the peel strength of the secondary battery separator prepared in this comparative example is reduced, and the longitudinal and transverse thermal shrinkage rates are increased. This is because under the vacuum drying conditions of this comparative example, PDA and PAA fail to undergo a cross-linking reaction, so that the MOFs nanoparticles cannot adhere well to the polymer film, ultimately resulting in poor peel strength between the MOFs nanoparticles and the polymer film, which in turn leads to an increase in thermal shrinkage and a decrease in thermal stability.
[0066] Comparative Example 4
[0067] A method for preparing a secondary battery separator is basically the same as Example 1, except that step (1.2) is not performed, and the PDA@ZIF-67 in step (2) is replaced by an equal mass of MOFs nanoparticles prepared in this comparative example.
[0068] The surface density of the secondary battery separator finally obtained is 7.38 g / m 2The electrolyte absorption rate is 534%, the ion conductivity is 1.38mS / cm, the peel strength is 56N / m, the longitudinal heat shrinkage rate is 5.6% after being placed at 150℃ for 1h, and the transverse heat shrinkage rate is 5.1% after being placed at 150℃ for 1h.
[0069] Example 2
[0070] A method for preparing a secondary battery separator, comprising the following steps:
[0071] (1) Preparation of PDA@ZIF-67;
[0072] (1.1) Dissolving cobalt nitrate hexahydrate and 2-methylimidazole in anhydrous methanol to obtain solution A and solution B, respectively. Mixing solution A and solution B, reacting at 20°C and normal pressure for 12 hours, and post-treating (centrifugation, washing, drying) to obtain MOFs nanoparticles; wherein the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:8, the drying temperature is 80°C, and the drying time is 6 hours;
[0073] The porosity of the obtained MOFs nanoparticles is 69% and the specific surface area is 749m 2 / g, average pore size is 17nm;
[0074] (1.2) dopamine, water, and tris(hydroxymethylaminomethane) hydrochloride buffer were mixed to prepare a precursor solution with a pH value of 8, and the MOFs nanoparticles prepared in step (1.1) were added thereto and subjected to self-polymerization reaction at 20°C for 1 hour to obtain PDA@ZIF-67; wherein the concentration of dopamine in the precursor solution was 3 mg / mL, and the concentration of the buffer solution in the precursor solution was 0.1 mol / L;
[0075] The thickness of the PDA coating layer in the obtained PDA@ZIF-67 was 4 nm;
[0076] (2) First, 25 wt% of PDA@ZIF-67 prepared in step (1), 1.7 wt% of carboxymethyl cellulose (manufacturer: Xinxiang Jinbang Power Technology Co., Ltd., brand: BVH9), 0.2 wt% of sodium dodecyl sulfate and the remainder of water were mixed evenly to obtain a slurry, and then the slurry was coated on one side of a polyethylene separator (porosity: 40%, thickness: 7 μm) by micro-gravure coating, and then vacuum dried at 60°C for 12 h to prepare a separator for a secondary battery; wherein the thickness of the coating on one side was 4 μm.
[0077] The surface density of the secondary battery separator finally obtained is 6.95 g / m 2The electrolyte absorption rate is 598%, the ion conductivity is 1.44mS / cm, the peel strength is 115N / m, the longitudinal heat shrinkage rate is 1.8% after being placed at 150℃ for 1h, and the transverse heat shrinkage rate is 1.6% after being placed at 150℃ for 1h.
[0078] Example 3
[0079] A method for preparing a secondary battery separator, comprising the following steps:
[0080] (1) Preparation of PDA@ZIF-67;
[0081] (1.1) Dissolving cobalt nitrate hexahydrate and 2-methylimidazole in anhydrous methanol to obtain solution A and solution B, respectively. Mixing solution A and solution B, reacting at 30°C and normal pressure for 24 hours, and post-treating (centrifugation, washing, drying) to obtain MOFs nanoparticles; wherein the molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole is 1:6, the drying temperature is 60°C, and the drying time is 12 hours;
[0082] The porosity of the obtained MOFs nanoparticles is 58% and the specific surface area is 471m 2 / g, average pore size is 18nm;
[0083] (1.2) dopamine, water, and tris(hydroxymethylaminomethane) hydrochloride buffer were mixed to prepare a precursor solution with a pH value of 9, and the MOFs nanoparticles prepared in step (1.1) were added thereto and subjected to self-polymerization reaction at 30°C for 4 hours to obtain PDA@ZIF-67; wherein the concentration of dopamine in the precursor solution was 2 mg / mL, and the concentration of the buffer solution in the precursor solution was 0.1 mol / L;
[0084] The thickness of the PDA coating layer in the obtained PDA@ZIF-67 was 4 nm;
[0085] (2) First, 35 wt% of the PDA@ZIF-67 prepared in step (1), 2.2 wt% of alginate (sodium alginate, manufactured by McLean's reagent, brand S817374), 0.2 wt% of dodecyl sulfuric acid and the remainder of water are mixed evenly to obtain a slurry, and then the slurry is coated on one side of a polyethylene separator (porosity of 40%, thickness of 9 μm) by micro-gravure coating, and then vacuum dried at 30°C for 24 h to prepare a separator for a secondary battery; wherein the thickness of the coating on one side is 3 μm.
[0086] The surface density of the secondary battery separator finally obtained is 7.25 g / m 2The electrolyte absorption rate is 618%, the ion conductivity is 1.48mS / cm, the peel strength is 107N / m, the longitudinal heat shrinkage rate is 1.9% after being placed at 150℃ for 1h, and the transverse heat shrinkage rate is 1.9% after being placed at 150℃ for 1h.
[0087] Example 4
[0088] A method for preparing a secondary battery separator, comprising the following steps:
[0089] (1) Preparation of PDA@ZIF-8;
[0090] (1.1) Dissolving zinc nitrate hexahydrate and 2-methylimidazole in anhydrous methanol to obtain solution A and solution B, respectively, mixing solution A and solution B, reacting at 150°C and normal pressure for 24 hours, and obtaining MOFs nanoparticles after post-treatment (centrifugation, washing, and drying); wherein the molar ratio of zinc nitrate hexahydrate to 2-methylimidazole is 1:10, the drying temperature is 80°C, and the drying time is 12 hours;
[0091] The porosity of the obtained MOFs nanoparticles is 81% and the specific surface area is 1123m 2 / g, average pore size is 4nm;
[0092] (1.2) dopamine, water, and phosphate buffer are mixed to prepare a precursor solution with a pH value of 8, the MOFs nanoparticles prepared in step (1.1) are added thereto, and the mixture is subjected to self-polymerization reaction at 25°C for 12 hours to obtain PDA@ZIF-8; wherein the concentration of dopamine in the precursor solution is 1 mg / mL, and the concentration of the buffer solution in the precursor solution is 0.1 mol / L;
[0093] The thickness of the PDA coating layer in the obtained PDA@ZIF-8 was 8 nm;
[0094] (2) First, 15 wt% of PDA@ZIF-8 prepared in step (1), 1 wt% of carboxymethyl cellulose (manufacturer: Xinxiang Jinbang Power Technology Co., Ltd., brand name BVH9), 0.1 wt% of sulfosuccinate (manufacturer: Huayu Fine Chemical Co., Ltd., brand name FS403 MES) and the remainder of water were mixed evenly to obtain a slurry, and then the slurry was coated on one side of a polyethylene separator (porosity of 45% and thickness of 16 μm) by wire rod coating, and then vacuum dried at 80° C. for 8 h to prepare a separator for a secondary battery; wherein the thickness of the coating on one side was 2 μm.
[0095] The surface density of the secondary battery separator finally obtained is 9.34 g / m 2The electrolyte absorption rate is 623%, the ion conductivity is 1.31mS / cm, the peel strength is 103N / m, the longitudinal heat shrinkage rate is 1.6% after being placed at 150℃ for 1h, and the transverse heat shrinkage rate is 1.5% after being placed at 150℃ for 1h.
[0096] Example 5
[0097] A method for preparing a secondary battery separator, comprising the following steps:
[0098] (1) Preparation of PDA@MOF-5;
[0099] (1.1) Dissolving zinc nitrate hexahydrate and terephthalic acid in N,N-dimethylformamide to obtain solution A and solution B, respectively; mixing solution A and solution B, reacting at 130°C and normal pressure for 15 hours, and obtaining MOFs nanoparticles through post-treatment (centrifugation, washing, and drying); wherein the molar ratio of zinc nitrate hexahydrate to terephthalic acid is 1:1, the drying temperature is 20°C, and the drying time is 24 hours;
[0100] The porosity of the obtained MOFs nanoparticles is 79% and the specific surface area is 1041m 2 / g, average pore size is 7nm;
[0101] (1.2) dopamine, water, and bicarbonate buffer were mixed to prepare a precursor solution with a pH value of 9.5, and the MOFs nanoparticles prepared in step (1.1) were added thereto and subjected to self-polymerization reaction at 40°C for 24 hours to obtain PDA@MOF-5; wherein the concentration of dopamine in the precursor solution was 2 mg / mL, and the concentration of the buffer solution in the precursor solution was 0.1 mol / L;
[0102] The thickness of the PDA coating layer in the obtained PDA@MOF-5 was 12 nm;
[0103] (2) First, 40 wt% of the PDA@MOF-5 prepared in step (1), 6 wt% of PAA (manufacturer: Fujian Blue Ocean Black Stone New Material Technology Co., Ltd., brand name BOBSive 288C), 0.5 wt% of sulfosuccinate (manufacturer: Huayu Fine Chemical Co., Ltd., brand name FS403 MES) and the remainder of water were mixed evenly to obtain a slurry, and then the slurry was coated on one side of a polyethylene separator (porosity of 45% and thickness of 16 μm) by wire rod coating, and then vacuum dried at 100° C. for 8 h to prepare a separator for a secondary battery; wherein the thickness of the coating on one side was 2 μm.
[0104] The surface density of the secondary battery separator finally obtained is 9.16 g / m 2The electrolyte absorption rate is 578%, the ion conductivity is 1.29mS / cm, the peel strength is 108N / m, the longitudinal heat shrinkage rate is 1.7% after being placed at 150℃ for 1h, and the transverse heat shrinkage rate is 1.7% after being placed at 150℃ for 1h.
Claims
1. A method for preparing a secondary battery separator, comprising coating a slurry on the surface of a polymer film and vacuum drying the slurry to prepare a secondary battery separator, wherein: The slurry contains 15-40wt% PDA@MOFs, 1-6wt% binder and water; PDA@MOFs are PDA-coated MOFs nanoparticles; The binder is a carboxyl binder; The vacuum drying temperature is 20-150°C and the time is 8-24h.
2. The method for preparing a secondary battery separator according to claim 1, characterized in that: The thickness of the PDA coating layer in PDA@MOFs is 1-30nm; the preparation steps of PDA@MOFs are as follows: (a) dissolving a metal salt and an organic ligand in a solvent to obtain a solution A and a solution B respectively, mixing the solution A and the solution B and reacting them, and obtaining MOFs nanoparticles after post-treatment; (b) Dopamine, water and buffer solution are mixed to prepare a precursor solution, into which MOFs nanoparticles are added for self-polymerization to obtain PDA@MOFs.
3. The method for preparing a secondary battery separator according to claim 2, characterized in that: In step (a), the metal salt is a Co salt or a Zn salt; The organic ligand is a nitrogen-containing heterocyclic ligand or a carboxylic acid ligand; The molar ratio of the metal salt to the organic ligand is 1:1-10; The reaction temperature is 20-150°C and the reaction time is 8-24h; The porosity of MOFs nanoparticles is 58-81% and the specific surface area is 471-1123m 2 / g, pore size is 4-18nm; In step (b), the buffer is tris hydrochloride buffer, phosphate buffer or bicarbonate buffer; The concentration of dopamine in the precursor solution is 1-3 mg / mL; The pH value of the precursor solution is 8-9.5; The self-polymerization reaction temperature is 20-40°C, and the self-polymerization reaction time is 1-24h.
4. The method for preparing a secondary battery separator according to claim 1, characterized in that: The carboxyl-based binder is one or more of PAA, carboxymethyl cellulose, and alginate.
5. The method for preparing a secondary battery separator according to claim 1, characterized in that: The slurry also contains 0.1-0.5wt% of a surfactant.
6. The method for preparing a secondary battery separator according to claim 1, characterized in that: The polymer membrane is a polyolefin membrane, a cellulose membrane, a polyimide membrane or a polyacrylonitrile membrane, and has a thickness of 7-16 μm.
7. The method for preparing a secondary battery separator according to claim 1, characterized in that: The slurry is coated on one side or both sides of the polymer film, and the thickness of the coating on one side is 2-4 μm.
8. The method for preparing a secondary battery separator according to claim 1, characterized in that: The coating is carried out by micro-gravure coating or wire rod coating.
9. A secondary battery separator, characterized in that: The secondary battery diaphragm is prepared by the method for preparing the secondary battery diaphragm according to any one of claims 1 to 8.
10. A secondary battery separator according to claim 9, characterized in that: The surface density of the secondary battery separator is 6-10g / m 2 The electrolyte absorption rate is 578-653%, the ion conductivity is 1.29-1.52mS / cm, the peel strength is 100-120N / m, the longitudinal heat shrinkage rate is <2% after being placed at 150℃ for 1h, and the transverse heat shrinkage rate is <2% after being placed at 150℃ for 1h.
Citation Information
Patent Citations
Selective oxygen permeating membrane as well as preparation method and application thereof
CN110449139A
MOF coating self-growing diaphragm and preparation method thereof
CN117293480A
Method for preparing zeolite imidazole skeleton modified aramid nanofiber modified diaphragm
CN118970366A
Separator for electrochemical device and electrochemical device including the same
US20240322370A1
Cited By
Composite diaphragm, preparation method thereof and secondary battery
CN120879150A
Secondary battery and electric device
CN122338225A